Pengaruh Current Ratio, Debt To Equity Ratio, Dan Total Asset Turnover Terhadap Return On Asset Pada PT. Astra International TBK Periode 2008-2017 - Nova Novita Sari (Universitas Batanghari Jambi, 2019)
This study aims to determine how the influence of the current ratio, debt to equity ratio and total asset turnover on return on assets at PT. Astra International Tbk simultaneously and partially. In this study using descriptive quantitative method which is a form of research data analysis to test the generalization of research results based on one sample. Descriptive analysis is carried out to obtain clarity about the characteristics of the variables under study or to describe the behavior of the observed variables based on statistical data obtained. The analytical tool used in this study is to use multiple linear regression with proof of the hypothesis with statistical tests f and statistical tests t. The results of the study indicate that the current ratio, debt to equity ratio and total asset turnover simultaneously have a significant effect on return on assets, which is proven by the value of 8.076>ftabel 4.76 and the significant value of 0.016 is smaller than the value of 0.05. While the results of the research show that the current ratio and the debt to equity ratio partially do not have a significant effect on return on assets which is proven by the value of T -0.445 <Ttable 2.446 with a significant value of 0.672> 0.05, the hypothesis is rejected so that the current ratio does not have a significant effect on return on assets. This is evidenced by the value of -1.182 <Ttable 2.446 with a significant value of 0.282> 0.05, the hypothesis is rejected so that the debt to equity ratio is not significantly affected by return on assets. While total asset turnover has a significant effect on return on assets, this is evidenced by the value of t hitung 2,998> 2,446 with a significant value of 0.024 <0.05. While the determination coefficient value is 0.802 or 80.2%, this means that 80.2% of the variation in ROA can be explained by variations of the three independent variables namely CR, DER and TATO while the remaining 19.8% is explained by other reasons outside the model.